SILVER IN PROTEROZOIC COMPLEXES OF THE WESTERN PART OF UKRAINIAN SHIELD (PECULIARITIES OF DISTRIBUTION, MINERALOGIC-GEOCHEMICAL ASPECTS) - HRINCHENKO, O.; BONDARENKO, S.; SOMKA, V.; BONDARENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper considers features of formation of silver mineralization in proterozoic complexes of the Ukrainian Shield. In many cases the manifestations of silver mineralization are spatially associated with deposits of uranium, rare metals, polymetals and gold, forming complex ores that can raise their economic importance substantially.